"When I am in Japan, I feel as though I’m not disabled": A cross-cultural adjustment study of trainees with disabilities from Asia-Pacific regions - Iwakuma, Miho; Okuhira, Masako; Nasu, Satomi (Disability Studies Quarterly, 2016)
This study aims to examine the cross-cultural adjustment processes of trainees with disabilities from Asia-Pacific regions, with the aim to explore factors that influence cross-cultural adjustments and uncover experiences by individuals with disabilities. We interviewed a total of 13 trainees, some of whom were interviewed multiple times. Several factors (e.g., affluence of the Japanese lifestyle, maintaining contact with home via the Internet, and/or previous knowledge of the host culture) greatly affected their transitions to Japan. Notably, participant adjustments were made on several different levels, including physical, social, and attitudinal.